2021
DOI: 10.7554/elife.72276
|View full text |Cite
|
Sign up to set email alerts
|

Proximity labeling identifies LOTUS domain proteins that promote the formation of perinuclear germ granules in C. elegans

Abstract: The germ line produces gametes that transmit genetic and epigenetic information to the next generation. Maintenance of germ cells and development of gametes require germ granules—well-conserved membraneless and RNA-rich organelles. The composition of germ granules is elusive owing to their dynamic nature and their exclusive expression in the germ line. Using Caenorhabditis elegans germ granule, called P granule, as a model system, we employed a proximity-based labeling method in combination with mass spectrome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 94 publications
1
13
0
Order By: Relevance
“…Together, these results suggest that one or both sdg-1 loci are subject to heritable changes upon loss of SID-1-dependent gene regulation, the direction of change might depend upon the levels of sdg-1 mRNA, and maintenance of these changes requires a DEPS-1-dependent mechanism. The expression states observed for SDG-1::mCherry and SDG-1 (Figures 4 and 5) could reflect a role for the SDG-1 protein in piRNA-mediated regulation, potentially through interactions with the Z-granule component ZSP-1/PID-2 62 and/or the germ granule-associated protein DEPS-1 63 . Specifically, high levels of SDG-1::mCherry protein produced from sdg-1::mCherryΔpi as a result of reduced piRNA-mediated silencing of mCherry as a foreign sequence 64 could result in a state of enhanced piRNA-mediated regulation within the germline.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these results suggest that one or both sdg-1 loci are subject to heritable changes upon loss of SID-1-dependent gene regulation, the direction of change might depend upon the levels of sdg-1 mRNA, and maintenance of these changes requires a DEPS-1-dependent mechanism. The expression states observed for SDG-1::mCherry and SDG-1 (Figures 4 and 5) could reflect a role for the SDG-1 protein in piRNA-mediated regulation, potentially through interactions with the Z-granule component ZSP-1/PID-2 62 and/or the germ granule-associated protein DEPS-1 63 . Specifically, high levels of SDG-1::mCherry protein produced from sdg-1::mCherryΔpi as a result of reduced piRNA-mediated silencing of mCherry as a foreign sequence 64 could result in a state of enhanced piRNA-mediated regulation within the germline.…”
Section: Main Textmentioning
confidence: 99%
“…69 ). To determine if the identification of SDG-1 as a potential interactor of the Z-granule component PID-2 62 /ZSP-1 52 and in proximity to the P-granule-adjacent protein DEPS-1 63 could be seen as colocalization in vivo , we examined the localization of SDG-1::mCherry within the cytoplasm at higher resolution using AiryScan imaging 70 . SDG-1::mCherry was enriched in perinuclear foci in many animals (Figure 6C, top ; 7 of 9 animals) and these sites of enrichment colocalized with the Z-granule marker GFP::ZNFX-1 (Figure 6C, bottom ; 100% colocalized in 10 of 12 animals with enrichment).…”
Section: Main Textmentioning
confidence: 99%
“…For our analysis, we used the non-specific biotin ligase TurboID, an improved version of the BirA enzyme with rapid labeling kinetics, The dot plot shows the brood size of individual worms in the indicated backgrounds which was fused to the C terminus of PTPN-22 (referred to hereafter as PTPN-22::TurboID) using CRISPR-based genome editing (49). As our control, we used N2 worms, which lack TurboID but contain an endogenous specific biotinylation activity that primarily targets four known carboxylases (MCCC-1, PCCA-1, PYC-1, and POD-2) (49)(50)(51)(52)(53).…”
Section: Proximity Labeling Identifies Candidate In Vivo Ptpn-22 Inte...mentioning
confidence: 99%
“…Recent reports showed that the loss of MIP-1/EGGD-1 disrupted perinuclear positioning of P granules, Z granules and Mutator foci, and induced the mislocalization of these subcompartments within the adult gonad 45,46,71 . Here, we examined whether the LOTUS domain MIP-1/EGGD-1 is required for the assembly and perinuclear localization of other germ granule subcompartments.…”
Section: The Lotus Domain Protein Mip-1/eggd-1 Sculptures the Archite...mentioning
confidence: 99%